PROMISING AREAS FOR THE DEVELOPMENT OF THE CRYPTOCURRENCY INDUSTRY IN UKRAINE AS A TOOL FOR INTENSIFYING FOREIGN TRADE ACTIVITIES OF ENTREPRENEURIAL STRUCTURES - Hedegaard, Michael; Daher Kаtherina; Hrytsenko, Larysa; Nikitchenko, Yevhen; Chumak, Olha (Socio-economic relations in the digital society, 2023)
In recent years, the cryptocurrency industry has been developing rapidly, creating new opportunities and challenges for investors, entrepreneurs, and policymakers. Ukraine has become a promising destination for investment in cryptocurrencies and blockchain development due to its favorable business environment, highly educated workforce, and growing technology sector. Organizational and economic support for the development of foreign trade activities of Ukrainian businesses in the context of the cryptocurrency industry includes a thorough analysis and development of strategies to use these opportunities. In this article, we have considered some promising areas for the development of the cryptocurrency industry in Ukraine using general scientific and special methods of scientific knowledge, such as analytical methods, comparative analysis, methods of comparison, and generalization. From the potential of blockchain-based e-government services to the possibilities of mining and trading cryptocurrencies, the article examines the country’s strengths and opportunities in this area and identifies ways to use them for future growth. To this end, the author analyzes the legal framework, the state and degree of development of the blockchain, the peculiarities and pace of mining, the degree of acceptance of cryptocurrencies in society, and the state and peculiarities of the development of cryptocurrency exchanges. Understanding the potential of the cryptocurrency industry in Ukraine, we believe that the strategic directions for promoting economic growth and technological innovation in the country are: a clear regulatory framework, a skilled workforce, abundant energy resources, and a growing number of cryptocurrency changes. These elements of organizational and economic support will help Ukrainian businesses to develop their foreign trade activities in the context of the growing influence of the cryptocurrency sphere, providing greater opportunities for investment and trade, as well as promoting the introduction of innovative technologies and increasing international competitiveness.